The Effectiveness of Social Media Marketing in Building Brand Awareness for Startups - Ina Karuehni; Peridawaty; Noorjaya Nahan; Rita Yuanita Toendan; Hansly Tunjang (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to analyze the effect of social media as a marketing tool on brand awareness in startups. Using quantitative methods, this study collected data through questionnaires distributed to consumers who interacted with startups on social media platforms. Multiple linear regression analysis was used to evaluate the influence of frequency of social media use, content type, interaction with consumers, and duration of use on brand awareness. The results showed that all independent variables had a positive and significant influence, with creative content type as the most influential factor. The study found that consistency in the frequency of social media use and active interaction with consumers also contributed significantly to increased brand recognition. Although the duration of social media use showed a positive influence, there were 30.8% of other variables not identified in this study, such as word-of-mouth and offline marketing strategies. These findings emphasize the importance for startups to utilize social media effectively in building brand awareness, while considering other factors that can affect brand recognition.